Completing Europe's banking union: Economic requirements and legal conditions - Thorsten Beck; Jan Pieter Krahnen; Philippe J. Martin; Franz C. Mayer; Jean Pisani-Ferry; Tobias Tröger; Beatrice Weder; Nicolas Véron; Jeromin Zettelmeyer (Bruegel, 2022)
The European Union's banking union project started in mid-2012 in response to the euro-area crisis, with the goal of breaking the bank-sovereign vicious circle. The objective was also to restore private liability in banking and to move towards an integrated supranational market for banking services. For all the progress achieved in the past decade, particularly in banking supervision, these aims have not yet been accomplished. This Policy Contribution analyses the deficiencies of the current framework and identifies possible responses, in line with three levels of reform ambition. We label these 'incremental' (broadening the scope for private-sector burden-sharing in future cases of bank failures), 'real' (effectively breaking the bank-sovereign vicious circle), and 'cosmic' (a single, seamlessly integrated banking market). European policymakers should set their sights on the second level, which we view as achievable within the current decade, requiring new EU legislation but no change to the European treaties.
Keywords: 330